2017
DOI: 10.1136/sextrans-2016-052921
|View full text |Cite
|
Sign up to set email alerts
|

Does maternal HSV-2 coinfection increase mother-to-child transmission of HIV? A systematic review

Abstract: BackgroundReducing HIV mother-to-child transmission (MTCT) is critical to ending the HIV pandemic. Reports suggest that herpes simplex virus-2 (HSV-2), a common coinfection in HIV-infected individuals, is associated with increased MTCT, but results have been conflicting. We conducted a systematic review of observational studies to quantify the magnitude of this relationship (PROSPERO no. CRD42016043315).MethodsWe searched Medline (1981 to June week 3, 2016), EMBASE (1981 to week 26, 2016), relevant conferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
5
0
3
Order By: Relevance
“…A systematic review has demonstrated a correlation between a herpes simplex virus type 2 (HSV‐2) diagnosis and HIV vertical transmission (odds ratio [OR] 1.57). However, studies did not always adjust for key confounders such as ART use and mode of delivery .…”
Section: Screening and Monitoring Of Pregnant Women Living With Hivmentioning
confidence: 99%
“…A systematic review has demonstrated a correlation between a herpes simplex virus type 2 (HSV‐2) diagnosis and HIV vertical transmission (odds ratio [OR] 1.57). However, studies did not always adjust for key confounders such as ART use and mode of delivery .…”
Section: Screening and Monitoring Of Pregnant Women Living With Hivmentioning
confidence: 99%
“…The development of preventive and therapeutic vaccines against Herpes Simplex Virus (HSV) is a global health priority for many reasons: (1) genital herpes affects half a billion people between the ages of 15 and 49 worldwide [ 1 , 2 ], causing diseases which are particularly severe and potentially lethal in newborns and immunocompromised hosts; (2) HSV infection is one of the worldwide leading causes of encephalitis, with high hospitalization and mortality rates when compared with other etiologic causes, especially in immunosuppressed and elderly hosts [ 3 , 4 ]; (3) HSV-1 and 2 infections have also been associated with the onset and morbidity of different non-communicable diseases, such as Alzheimer’s disease [ 5 ] and atherosclerosis [ 6 ] and with an increased risk of horizontal and vertical HIV acquisition and transmission [ 7 , 8 ] and bacterial vaginosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these genital lesions favor acquisition of other STIs, in particular, human immunodeficiency virus type 1 (HIV1) . Shedding of HSV2 from the genital tract is recurrent and asymptomatic . Intermittent antiviral therapy can suppress current infections while prophylactic use can prevent further relapses.…”
Section: Introductionmentioning
confidence: 99%